Efektivitas Hiperoksigenasi Pre-Post Suction Pada Pasien Acute Decompesated Heart Failure terhadap Saturasi Oksigen: Case Study - Paparang, Syallom Mita; Paat, Toar Calvin Christo; Malara, Reginus Tertius (Mapalus Nursing Science Journal, 2025)
Abstract Background. Acute Decompensated Heart Failure (ADHF) causes decreased cardiac output to respiratory failure requiring mechanical ventilation. However, this condition causes increased secretions due to the inability to cough spontaneously, so suction is needed to maintain a patent airway. Pre- and post-suction hyperoxygenation is important to avoid complications of hypoxemia and hemodynamic disorders. Objective. This scientific paper aims to analyze nursing care providing pre- and post-suction hyperoxygenation interventions in ADHF patients with nursing problems of Ineffective Airway Clearance. Method. This scientific paper is made in the form of a case study with a sample of Mr. FM. Implementation is carried out by administering hyperoxygenation for 1 minute pre-post suction. Evaluation using a bedside monitor by monitoring hemodynamic parameters such as Mean Arterial Pressure (MAP), heart rate (HR) and oxygen saturation (SpO2). Results. The results of the intervention for 2 days of administering 1 minute pre- and post-suction hyperoxygenation showed changes in oxygenation status, hemodynamic parameters, and the amount of airway secretions. Conclusion. Based on the evaluation results, hyperoxygenation for 1 minute pre and post suction was proven effective in maintaining oxygenation and hemodynamic stability within the normal range in ADHF patients with ventilators as seen from the MAP, HR and SpO2 parameters. Keywords: Acute decompensated heart failure, case study, hyperoxygenation, suction.